Frequency of Cardiometabolic Risk Factors Among Young People with Type 2 Diabetes Mellitus at Tertiary Care Unit Karachi, Pakistan - Abbas Bhatti, Kanwal; Musarrat Riaz; Saima Askari; Abdul Basit (Pakistan Armed Forces Medical Journal, 2023)
Objective: To determine the frequency of Cardiometabolic Risk Factors (CMRF) among young people with T2DM presenting at the Tertiary Care Unit in Karachi, Pakistan. Study Design: Retrospective longitudinal study. Place and Duration of Study: Baqai Institute of Diabetology and Endocrinology (BIDE), a Tertiary Care Unit, Karachi Pakistan, from Jan 2000 to Dec 2019. Methodology: The data of participants with diabetes (PWD) aged 18-45 years on the first visit was extracted from the computerized Health Management System (HMS). The demographics, anthropometric, biochemical, and medical information on obesity, smoking, hypertension, dyslipidemia, HbA1c, and family history of diabetes were gathered. Results: The study comprised 5336 participants with diabetes with a mean age of 31.94±5.52 years. High frequency of obesity, hypertension, dyslipidemia, cigarette smoking, poor glycemic control, and a positive family history of diabetes were observed, and their associations were statistically significant. Out of these, 4114(77.1%) were obese, 1663(31.4%) were hypertensive, 585(11%) were smokers, 4162(78%) had a positive family history of diabetes, 2519(47.2%) had HbA1c >10%, 2113(39.6%) had HbA1c between 7-10%. For dyslipidemia, 3383(63.4%) had high triglycerides, 3202(60%) had high LDL-C, 4578(85.8%) had low HDL-C, and 1729(32.4%) had high total cholesterol. Conclusion: The results validate the importance of early screening for CMRF in young diabetics for management and complications prevention in the early stages of the disease and advocate screening for CMRF in health care policy.